Improved Leadership Skills and Aptitudes in an Excellence EMBA Program: Creating Synergies With Dialogic Leadership to Achieve Social Impact - Campos, José Antonio; Aubert, Adriana; Guo, Mengna; Joanpere, Mar (Frontiers in Psychology, 2020)
Psychological research on leadership has demonstrated to achieve social impact, particularly in the improvement of working environments and organizational performance. The understanding of the organizational context of leader behavior and its different components becomes crucial to analyze the impact of leadership in organizations. The purpose of this study is to identify and analyze the transformation and change of leadership skills and aptitudes before and after the implementation of an excellence EMBA programme, particularly in relation to two components of the organizational context: 1) goals and purposes, 2) people and groups. Data were collected from open-ended questionnaires to alumni and current participants in an executive MBA programme (EMBA) enrolled in leadership courses. The emerging issues identified in the responses include themes linked to dialogic leadership, and show that participants improve their leadership skills and aptitudes, advancing towards the effective leadership and potential social impact in their organizations. The article finalizes in a discussion identifying synergies with current developments of psychological research in leadership and social impact of science.